Influence of Moringa Leaf Powder on Growth, And Blood Biochemistry in Growing Japanese Quails - Amen, Sameerah H. (American Journal of Biology and Natural Sciences, 2025)
The aim of this study was to determine the effect of different quantities of Moringa oleifera leaf powder supplementation (MOLP) on growth performance, feed intake, feed conversion ratio (FCR), and blood biochemistry of Japanese quail. Three hundred-twenty quails were randomly divided into 4 treatment groups, with 80 birds for each group and MOLP inclusion levels (0, 2.5, 5, and 7.5) %. The four weeks experiment included the quail, which were kept in single cages where they were raised under common environmental conditions. The assessment of growth was performed through regular measurements of performance metrics such as body weight, feed consumption, and FCR at regular intervals. Blood at the conclusion of the experiment was carried out to characterize biochemical analytically such as (Uric acid, glucose, total cholesterol, albumin, total protein and globulin). The data also showed there was no difference in body weight, blood biochemistry, and FCR between groups of treatment (P≤0.05). FI intake (FI) was much higher in experimental (Period 1, 2) periods, and more so for 2.5% group, and this effect decreased with time, and no significant differences remained in period 4. Finally, period 2 and 4 showed the efficiency highest for feed conversion with T4 (7.5%), but not in all times period. The result showing that the supplementation of Moringa does not affect the experimental quality of Japanese quail, including its key traits and performance-biochemical results, at both the time and level, is indicative of low inclusion level or adaption over time. More research has to be done with increased levels of inclusion with long-lasting feeding periods, to fully appreciate the effectiveness of nutritional significance of Moringa supplementation in poultry feedings.